Mortality in New Zealand workers exposed to phenoxy herbicides and dioxins. Issue 1 (21st December 2004) - 't Mannetje, A; McLean, D; Cheng, S; Boffetta, P; Colin, D; Pearce, N
Abstract : Aims: To evaluate mortality in New Zealand phenoxy herbicide producers and sprayers exposed to dioxins. Methods: Phenoxy herbicide producers (n = 1025) and sprayers (n = 703) were followed up from 1 January 1969 and 1 January 1973 respectively to 31 December 2000. A total of 813 producers and 699 sprayers were classified as exposed to dioxin and phenoxy herbicides. Standardised mortality ratios (SMR) were calculated using national mortality rates. Results: At the end of follow up, 164 producers and 91 sprayers had died. Cancer mortality was reduced for sprayers (SMR = 0.82, 95% CI 0.57 to 1.14) and increased in exposed production workers (SMR = 1.24, 95% CI 0.90 to 1.67), especially for synthesis workers (SMR = 1.69), formulation and lab workers (SMR = 1.64), and maintenance/waste treatment/cleaning workers (SMR = 1.46). Lymphohaematopoietic cancer mortality was increased in exposed production workers (SMR = 1.65, 95% CI 0.53 to 3.85), especially for multiple myeloma (SMR = 5.51, 95% CI 1.14 to 16.1). Among sprayers, colon cancer (SMR = 1.94, 95% CI 0.84 to 3.83) showed increased mortality. Conclusions: Results showed 24% non-significant excess cancer mortality in phenoxy herbicide producers, with a significant excess for multiple myeloma. Associations were stronger for those exposed to multiple agents including dioxin during production. Overall cancer mortality was not increased for producers and sprayers mainly handling final technical products, although they were likely to have been exposed to TCDD levels far higher than those currently in the general New Zealand population.